2007
DOI: 10.1063/1.2798382
|View full text |Cite
|
Sign up to set email alerts
|

Bounds for the adiabatic approximation with applications to quantum computation

Abstract: We present straightforward proofs of estimates used in the adiabatic approximation. The gap dependence is analyzed explicitly. We apply the result to interpolating Hamiltonians of interest in quantum computing. * Electronic address: jansen@math.tu-berlin.de † Electronic address: seiler@math.tu-berlin.de ‡ Electronic address: Marybeth.Ruskai@tufts.edu

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
448
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(458 citation statements)
references
References 26 publications
8
448
0
2
Order By: Relevance
“…One possibility of such a stationary state is to assume the thermal equilibrium state (β −1 = k B T at temperature T ) [4] is performed by replacing (in the interaction picture) ρ S (t ′ ) → ρ S (t) under the integral, substituting τ = t − t ′ and extending the integration to infinity. This is usually motivated by fastly decaying reservoir correlation functions (9). By doing so, we obtain the BM Master Equatioṅ…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility of such a stationary state is to assume the thermal equilibrium state (β −1 = k B T at temperature T ) [4] is performed by replacing (in the interaction picture) ρ S (t ′ ) → ρ S (t) under the integral, substituting τ = t − t ′ and extending the integration to infinity. This is usually motivated by fastly decaying reservoir correlation functions (9). By doing so, we obtain the BM Master Equatioṅ…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the maximum transformation rate (where the final excitations are acceptably small) corresponds to the computational complexity of the adiabatic algorithm. For closed systems, it is related to the spectral properties of the time-dependent system Hamiltonian [9,10]. For a reservoir at sufficiently low temperatures, this scheme is thought to be robust against decoherence [6] and might even be aided by it [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work [19] has shown that the adiabatic condition may be a more complicated function of these parameters, but all of this recent work has the running time scaling like an inverse polynomial in g min . Since the norm of the Hamiltonian's derivative is usually independent of parameters such as our α and β, typically the gap is taken as the important part of this expression.…”
Section: Quantum Adiabatic Optimization Of Symmetric Functionsmentioning
confidence: 99%
“…Recently, two of the main results of this article, i.e., the optimal run-time scaling T = O(∆E −1 min ) and the fasterthan-polynomial decrease of the final error a 1 (T ), have been demonstrated rigorously for a class of Hamiltonians using methods of spectral analysis [20].…”
Section: Note Addedmentioning
confidence: 99%